Opportunity Evaluation as Rule‐Based Decision Making - Wood, Matthew S.; Williams, David W. (Journal of Management Studies, 2014)
AbstractWe draw from cognitive science literature on rule‐based thinking to develop and empirically test a theoretical framework of entrepreneurial opportunity evaluation. We argue that entrepreneurs make use of socially constructed rules to discern the attractiveness of an opportunity, for them, specifically. Using conjoint analysis data of 498 decisions made by 62 entrepreneurs, we find that entrepreneurs' use of rules regarding opportunity novelty, resource efficiency, and worst‐case scenario significantly influences entrepreneurs' evaluations of opportunities and that individual differences in opportunity market and technology knowledge augment the effect of the rules on opportunity attractiveness. Additionally, we document that the worst‐case scenario diminishes the positive effect of other rule criteria (e.g. novelty, resource efficiency) on opportunity evaluation and that market and technology knowledge further influence the negative effects of the worst‐case scenario.